Rediscovering the roots of Chinese thought : Laozi's philosophy - Chen, Guying (Contemporary Chinese scholarship in Daoist studies., 2015)
This book translates Lao Zhuang xinlun, a key work of contemporary Chinese. It offers a unique discussion of the Laozi, arguing-in contrast to standard Western scholarship-that the text goes back to a single author and identifying him as an older contemporary, and even teacher, of Confucius. This places the Confucian Analects after the Laozi and makes the text the most fundamental work of ancient Chinese thought. Chen explores these debates regarding these points, providing evidence based on materials excavated from Mawangdui and Guodian. His book is fascinating documentation of contemporary C.